PERAN UNDP DALAM SOCIO-ECONOMIC RECOVERY SEBAGAI BAGIAN PEACEBUILDING PASCA PERANG SIPIL DI LIBERIA TAHUN 2005-2011 - Bayu Pratama, Putu Odika; Dharmiasih, D.A. Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2016), 2016)
ABSTRACT Liberia’s civil war happened in two periods, first period was 1989-1997 and second period was 1998-2003. The socio-economical impacts themselves brought quality degradation of society life. The end of civil war was a momentum for Government of Liberia to open widely cooperation and receive assistances from external actors. One of international organizations that helped Government of Liberia was United Nations Development Programme (UNDP). The existence of UNDP in Liberia was to help and to give assistance in order to support post-conflict peacebuilding. Liberia’s condition after civil war supported socio-economic recovery as part of post-conflict peacebuilding. UNDP carried out roles as development agency and also humanitarian agency to help Government of Liberia through socio-economic recovery related programmes and activites. The roles of UNDP to support Government of Liberia was addressed to create sustainable peace from negative peace to positive peace. This study aims to describe the roles of UNDP through socio-economic recovery as part of post-conflict peacebuilding in Liberia. This paper is also studied using concepts of civil war, international organization, and peacebuilding. The locus of this study is from 2005 to 2011. Key words : UNDP, socio-economic recovery, peacebuilding